THE SYNERGY OF FISCAL AND MONETARY POLICY FOR REAL SECTOR - Ika Permatasari; Hendry Cahyono; Dwi Wulandari; Hadi Sumarsono (Universitas Hayam Wuruk Perbanas, 2013)
One of the causes of low growth and the real sector's contribution is economic policy, both fiscal and monetary that is lesssupportive of the economic actors in the real sector. From the fiscal side, the budget magnitudescan be seen to the realsector (e.g. Agriculture) that is less than 5 percent. The funds are still skimpy that assessed itis difficult todevelop the agricultural sector. From the monetary side, the interest rate is judged still too high and cause economic actors in the real sector is quite difficult to get capital access. This study aims to find synergies between fiscal and monetary policy to support the real sector. This research was using Analytical Hierarchy Process (AHP) through the distribution ofquestionnaires to respondents of SME in Surabaya. The results showedthat interest rate and capital accessto financial institutions are factors considered by SME in obtaining credit (monetary policy). On the other hand, raw materials subsidies and fuel are also a major concern for them to increase production output (fiscal policy).